Potential of UV/H2O2 oxidation for enhancing the biodegradability of municipal reverse osmosis concentrates - Liu, K (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
UVC/H2O2 and VUV/H2O2 oxidation processes were evaluated for the degradation of organic pollutants in reverse osmosis concentrate (ROC) produced from a municipal secondary effluent. It was found that the oxidation by UVC/H2O2 and VUV/H2O2 processes could be described as a pseudo first-order reaction. For UVC increased oxidation occurred with increasing H2O2 dosage up to 2 mM above which improvement in oxidation performance decreased. At the same H2O2 dosage, VUV irradiation gave better overall oxidation performance. Compared with UVC/6 mM H2O2, VUV/2 mM H2O2 gave a greater rate of reduction of chemical oxygen demand, but a lower rate for reduction of dissolved organic carbon, suggesting that oxidation of organics by the two methods followed different pathways. The change of absorbance at 254 nm and fluorescence excitation emission matrix spectra of irradiated samples indicated that the large and complex compounds were fragmented rapidly by the *OH, resulting in rapid decolourisation. The biodegradability of the organics in the ROC was increased from 11% to 35% after 1 h treatment by UVC/3 mM H2O2, whereas a greater increase (41%) was obtained with VUV/2 mM H2O2. This increase in biodegradability indicates the potential for employing a subsequent biological treatment process